Rebranding and Restructuring Strategy of Physics Education Study Program in PTS NTB: UNDIKMA Case Study - Dwi Pangga; I Wayan Lasnawan; I Gusti Putu Suharta; I Wayan Widiana; Cahyo Febri Wijaksono (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study investigates the declining enrollment trend in the Physics Education Study Program at Universitas Pendidikan Mandalika (UNDIKMA), a private higher education institution in West Nusa Tenggara, Indonesia. The objective is to identify the factors contributing to reduced student interest and to propose strategic interventions to revitalize the program amid increasing competition between public and private universities. Method: A mixed-methods approach was employed, combining longitudinal analysis of enrollment data with qualitative insights from interviews, surveys, and document reviews. Comparative data from similar study programs at both private and public universities in the region were also examined. Additionally, SWOT and TOWS analyses were conducted to generate strategic recommendations. Results: The findings reveal a consistent decline in enrollment, influenced by limited career prospects for physics education graduates, dominance of public universities in the region, outdated curricula, and weak promotional strategies. Comparative analysis underscores structural disparities in institutional reputation and resource allocation between private and public institutions. Novelty: This study highlights the urgent need for contextually adaptive strategies to sustain science-based teacher education in non-metropolitan regions. The proposed interventions—curriculum restructuring, digital rebranding, alum engagement, and hybrid learning formats—offer an integrated framework for enhancing program appeal. The research contributes to policy discourse on sustaining strategic academic programs in private institutions by emphasizing the importance of institutional identity and targeted communication.